Problematika Jadwal Waktu Salat Subuh di Indonesia - Abdul Mughits (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
Lately, the dawn prayer time schedule thats the mainstream in Indonesia "sued" by Qiblati community as still too early. It was based on testimony at several locations, while sounding the call to prayer, daybreak had not apperaed. High data used dawn sun for the Ministry of Religious Affairs and the majority of moslems in Indonesia is -20o. While the results of observations of experts in Indonesia and internationally under -20o, which ranges from -13,5o to -19,5o (difference 1o = 4 minutes). Of these issues, including "emergency" Islamic law that must be answered because it will have serious implications in legal matters of worship: legality of urging to prayer and women who stop menstruating (haid) or childbirth (nifas) in those times. Becouse this is the integration of religion and science phenomenon then Muslims should be open to make corrections thats supported by scientific data that can be accounted for shar'ie and science.